Rancang Bangun Sistem Informasi Pusat Tumbuh Kembang Anak Menggunakan Pendekatan Extreme Programming (Studi Kasus: Alfatih Center) - Muhammad Dzaki Ilhami; Sholihin (shofanah Media Berkah, 2026)
The Alfatih Center Child Development Clinic faces challenges in administrative management, which is done manually, leading to inefficiencies in record-keeping and errors in data management. This study aims to develop and implement an integrated web-based information system to effectively and efficiently manage patient records, therapy schedules, and clinic information. The software development methodology used is Extreme Programming (XP), which includes the planning, design, scripting, and testing phases. The technologies used in the development of this system include PHP, Laravel, MySQL, HTML, CSS, and JavaScript. The research findings indicate that the developed system enhances the effectiveness of administrative procedures, facilitates quick access to information, and minimizes data entry errors. This system also facilitates improved therapeutic services and simplifies public access to information about the clinic.